Algal Community Structure of the Yalour Mausoleum, Cemetery of La Plata, Buenos Aires, Argentina - Gómez de Saravia, Sandra Gabriela (2018)
Biological communities that form biofilms on buildings and monuments can not only discolor the surface, but also produced physical and chemical alterations. Although the type of microorganisms that colonize the facades of cement construction is diverse, the analyzes carried out in situ reveal that algae are one of the initial and main colonized. The algae can cause biochemical deterioration, since the produce, like fungi, metabolites of a predominantly organic nature. The Cemetery of La Plata, founded by Benoit in 1887, has in its interior mausoleums and notable monuments of various styles worthy of patrimonial protection. One of them is the Yalour mausoleum that is uniformly covered by a black patina, with conspicuous spots of lighter shade. Various chemicals with biocidal activity are commonly added to interior and exterior paint formulations to provide protection of algal growth. In order to select compounds that prevent and control biofilm formation, it is necessary to know what physiological activity they present. For this reason, the aim of this work was to characterize, from the biological point of view, the biofilm developed on the mausoleum.